2019
DOI: 10.1002/sim.8287
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the impact of sleep time on truck driver performance using a recurrent event model

Abstract: Driver fatigue is a major safety concern for commercial truck drivers and is directly related to the total hours of sleep prior to a working shift. To evaluate changes in driving performance over a long on-duty driving period, we propose a mixed Poisson process recurrent-event model with time-varying coefficients. We use data from 96 commercial truck drivers whose trucks were instrumented with an advanced in situ data acquisition system. The driving performance is measured by unintentional lane deviation event… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 71 publications
(78 reference statements)
0
11
0
Order By: Relevance
“…It has been shown that the off-duty sleeping groups have different SCE risk patterns over the 11-hour driving time. 9,10 The number of nondriving tasks had a mean of 2.86 (SD = 2.08) and a range of frequency from 0 to 13. We considered three shift starting time groups: 667 (36.1%) shifts started in the morning (5:00 AM-9:00 AM), 768 (41.6%) shifts started in the daytime (9:00 AM-8:00 PM), and 413 (22.3%) shifts started at night (8:00 PM-5:00 AM).…”
Section: Time-independent Variablesmentioning
confidence: 99%
See 4 more Smart Citations
“…It has been shown that the off-duty sleeping groups have different SCE risk patterns over the 11-hour driving time. 9,10 The number of nondriving tasks had a mean of 2.86 (SD = 2.08) and a range of frequency from 0 to 13. We considered three shift starting time groups: 667 (36.1%) shifts started in the morning (5:00 AM-9:00 AM), 768 (41.6%) shifts started in the daytime (9:00 AM-8:00 PM), and 413 (22.3%) shifts started at night (8:00 PM-5:00 AM).…”
Section: Time-independent Variablesmentioning
confidence: 99%
“…We adopt the B-splines with degree of 𝜈, which are widely used in recurrent event models with nonparametric intensity functions. 9,10,12 Let h l denote the number of knots and B lh (t) represent the value of the h th B-spline at t, where h = 1, … , H l and H l = h l + 𝜈. Then, the smooth function 𝛽 lj (t) is expressed by a linear combination of the B-spline basis functions B lh (t)'s given by 𝛽 lj…”
Section: Model Specificationmentioning
confidence: 99%
See 3 more Smart Citations